Method for culturing stem cells with bilayer composite hydrogel microcarrier

A two-layer hydrogel microcarrier with a specific inner and outer layer composition provides structural support and controlled nutrient release, addressing the instability issues of conventional gels to enhance stem cell culture efficiency.

JP2025015483AActive Publication Date: 2025-01-30何鈞軒
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024114381
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-02-22
Filing Date
2024-07-17
Publication Date
2025-01-30
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

Conventional gels used for stem cell culture are prone to collapse and have limited structural strength, leading to inefficient and unstable release of nutrients, which hampers the culture efficiency of stem cells.

Method used

A two-layer composite hydrogel microcarrier is developed, comprising an inner gel structure made from an ionic bridge of sodium alginate and carboxymethylcellulose with a weight ratio of 3:2, and an outer layer made from polymers like N, N-dimethyl acrylamide, which provides structural support and controlled release of nutrients.

Benefits of technology

The two-layer composite hydrogel microcarrier enhances the structural stability and extends the release time of nutrients, allowing for sustained culture of stem cells with improved efficiency and reduced burst release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015483000001_ABST
    Figure 2025015483000001_ABST
Patent Text Reader

Abstract

To provide a method for culturing stem cells with improved efficiency by using a gel that has improved structural strength and enables long-term and stable release of contents.SOLUTION: A bilayer composite hydrogel microcarrier includes: an inner layer gel structure obtained by ionically crosslinking an inner layer polymer with an inner layer crosslinker; and an outer layer gel structure obtained by covalently crosslinking an outer layer monomer with an outer layer crosslinker, which covers the inner layer gel structure; a first inner layer polymer being sodium alginate, a second inner layer polymer being carboxymethylcellulose, and a nutritional component being located inside the inner layer gel structure. The growth rate of stem cells is improved by controlling the composition of the bilayer composite hydrogel microcarrier, the weight ratio of sodium alginate to carboxymethylcellulose, and the location of the nutritional component. The structural strength can be ensured by controlling the weight percentage of carboxymethylcellulose.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to bilayer composite hydrogel microcarriers and methods for making and using same, and in particular to the use of bilayer composite hydrogel microcarriers for stem cell culture. [Background technology]

[0002] Gels have the property of releasing and delaying the release of the contents carried therein, and are widely used in the field of drug release. However, conventional gels are prone to collapse and have limitations such as insufficient structural strength, making it difficult to provide long-term and stable release of contents. Therefore, when gels are used for culturing stem cells, the efficiency of culturing stem cells is limited. Summary of the Invention [Problem to be solved by the invention]

[0003] Therefore, in order to improve the efficiency of stem cell culture, a problem to be solved is how to provide a gel with improved structural strength and extended release time. [Means for solving the problem]

[0004] In some embodiments of the present disclosure, there is provided a method for culturing stem cells using a bi-layer composite hydrogel microcarrier, the method comprising the steps of: providing stem cells, a bi-layer composite hydrogel microcarrier, and a nutrient component; mixing the stem cells, the bi-layer composite hydrogel microcarrier, and the nutrient component to obtain a gelling medium; and adding a culture solution to the gelling medium, the bi-layer composite hydrogel microcarrier comprising an inner layer gel structure obtained by ionically crosslinking an inner layer polymer with an inner layer crosslinker; and an outer layer gel structure obtained by covalently crosslinking and polymerizing an outer layer monomer with an outer layer crosslinker, the outer layer gel structure being covered with the inner layer gel structure, the inner layer polymer comprising a first inner layer polymer and a second inner layer polymer, the first inner layer polymer being sodium alginate, the second inner layer polymer being carboxymethylcellulose, the weight ratio of sodium alginate to carboxymethylcellulose being 3:2, the weight percentage of the carboxymethylcellulose being greater than 1% when the weight percentage of the inner layer gel structure is taken as 100%, and the nutrient component being located inside the inner layer gel structure.

[0005] In some embodiments, the stem cells include embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or combinations thereof.

[0006] In some embodiments, the inner layer gel structure is a plurality of inner layer sheet-like structures connected to each other and separated from each other by a plurality of inner layer holes, and the outer layer gel structure is a plurality of outer layer sheet-like structures connected to each other and separated from each other by a plurality of outer layer holes having pore sizes smaller than the pore size of each of the inner layer holes.

[0007] In some embodiments, the inner layer gel structure will be an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.

[0008] In some embodiments, the inner layer polymer and the inner layer crosslinked material have opposite electrical properties.

[0009] In some embodiments, the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide, or a combination thereof.

[0010] In some embodiments, the outer layer crosslinked comprises N,N'-methylenebisacrylamide.

[0011] In some embodiments, the weight percentage of sodium alginate is 0.1% to 5%, where the weight percentage of the inner layer gel structure is 100%.

[0012] In some embodiments, the weight percentage of the carboxymethyl cellulose is 1% to 5%, where the weight percentage of the inner layer gel structure is 100%.

[0013] In some embodiments, the nutritional ingredients include growth factors, vitamin A acid, penicillin, bovine serum albumin, or combinations thereof.

[0014] In some embodiments of the present disclosure, there is provided a method for culturing stem cells using a bi-layer composite hydrogel microcarrier, the method comprising the steps of: providing stem cells, a bi-layer composite hydrogel microcarrier, and a nutritional component comprising a polymeric protein having a molecular weight of at least 500 g / mol; mixing the stem cells, the bi-layer composite hydrogel microcarrier, and the nutritional component to obtain a gelling medium; and adding a culture solution to the gelling medium, the bi-layer composite hydrogel microcarrier comprising an inner layer gel structure obtained by ionically cross-linking an inner layer polymer with an inner layer crosslinker, and an outer layer gel structure obtained by covalently cross-linking and polymerizing an outer layer monomer with the outer layer crosslinker, the outer layer gel structure being coated with the inner layer gel structure, the inner layer polymer comprising a first inner layer polymer and a second inner layer polymer, the first inner layer polymer being sodium alginate, the second inner layer polymer being carboxymethylcellulose, the weight ratio of sodium alginate to carboxymethylcellulose being 3:2, and the nutritional component being located inside the inner layer gel structure.

[0015] In some embodiments, the stem cells include embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or combinations thereof.

[0016] In some embodiments, the inner layer gel structure is a plurality of inner layer sheet-like structures connected to each other and separated from each other by a plurality of inner layer holes, and the outer layer gel structure is a plurality of outer layer sheet-like structures connected to each other and separated from each other by a plurality of outer layer holes having pore sizes smaller than the pore size of each of the inner layer holes.

[0017] In some embodiments, the inner layer gel structure will be an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.

[0018] In some embodiments, the inner layer polymer and the inner layer crosslinked material have opposite electrical properties.

[0019] In some embodiments, the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide, or a combination thereof.

[0020] In some embodiments, the outer layer crosslinked comprises N,N'-methylenebisacrylamide.

[0021] In some embodiments, the weight percentage of sodium alginate is 0.1% to 5%, where the weight percentage of the inner layer gel structure is 100%.

[0022] In some embodiments, the weight percentage of carboxymethylcellulose is greater than 1%, based on the weight percentage of the inner layer gel structure being 100%.

[0023] In some embodiments, the weight percentage of the carboxymethyl cellulose is 1% to 5%, where the weight percentage of the inner layer gel structure is 100%. [Brief description of the drawings]

[0024] The above and other objects, features, advantages and embodiments of the present invention will become more apparent from the following description of the accompanying drawings. [Figure 1] FIG. 1 shows a gel state change diagram corresponding to changes in concentration and temperature when an ABA type triblock copolymer of poly(ε-caprolactone-co-glycolide) and poly(ethylene glycol; Tri-PCG) according to some embodiments of the present disclosure is stored in phosphate buffered saline. [Diagram 2] Electron microscope images of two-layer composite hydrogel microcarriers according to some embodiments of the present disclosure, where the top row a-c are the SA-CMC@PDMA-1 group, the second row d-f are the SA-CMC@PDMA-3 group, and the bottom row g-i are the SA-CMC@PAA-1 group. [Figure 3A] The water absorption and expansion properties of different inner layer gel structures are shown. [Figure 3B] 1 shows the water absorption and expansion properties of two-layer composite hydrogel microcarriers with different gel structures. [Figure 4A] 1 shows the cumulative release rate of the contents over time at different pH values ​​for bilayer composite hydrogel microcarriers with different gel structures. [Figure 4B] 1 shows the cumulative release rate of the contents over time at different pH values ​​for bilayer composite hydrogel microcarriers with different gel structures. [Figure 5A] 1 shows the cumulative release rate of the contents over time at different pH values ​​for bilayer composite hydrogel microcarriers with different gel structures. [Figure 5B] 1 shows the cumulative release rate of the contents over time at different pH values ​​for bilayer composite hydrogel microcarriers with different gel structures. [Figure 6A] 1 shows the cumulative release rate of the contents over time at different pH values ​​for bilayer composite hydrogel microcarriers with different gel structures. [Figure 6B]1 shows the cumulative release rate of the contents over time at different pH values ​​for bilayer composite hydrogel microcarriers with different gel structures. [Figure 7] FIG. 1 shows the viscosity vs. temperature plot of gel structures having different weight percentages of sodium alginate and carboxymethylcellulose. [Figure 8A] This shows the mRNA expression ratios corresponding to lipoprotein lipase (LPL) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) in adipose stem cells when adipose stem cells are cultured using gel structures with different weight ratios of sodium alginate and carboxymethylcellulose. [Figure 8B] Adipose stem cells were cultured using gel structures with different weight ratios of sodium alginate and carboxymethylcellulose, and the cell growth state diagrams under a microscope after staining the adipose stem cells reddish purple are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In order to complete the description of the present invention in detail, the following detailed description will be given of the embodiments and specific examples of the present invention, but they are not the only ways to implement or apply the specific examples of the present invention. Each of the examples disclosed below can be combined or substituted when beneficial, and one example can be added to another without the need for further description or explanation. In the following description, numerous specific details are described to enable the reader to fully understand the following examples. However, the embodiments of the present invention may be implemented without the specific details.

[0026] In this context, unless specifically limited, "a" and "the above" generally refer to one or more. As used herein, the terms "comprise," "include," "having," and similar words refer to the stated features, regions, integers, steps, operations, elements, and / or components, but should be understood to not exclude other features, regions, integers, steps, operations, elements, components, and / or groups thereof.

[0027] As used herein, the term "about" means that the value of the given quantity varies within 5% of that value (e.g., ±1%, ±2%, ±3%, ±4%, 5% of the value). These values ​​are merely examples and are not intended to be limiting. It should be understood that the term "about" may refer to a percentage of the value of the given quantity as interpreted by one of ordinary skill in the art in light of the teachings herein.

[0028] In this specification, unless otherwise specified, "%" is predefined as weight percent (wt%).

[0029] Although the methods disclosed herein are described below using a sequence of operations or steps, the order in which these operations or steps are presented should not be construed as limiting the invention. For example, some operations or steps may be performed in different orders and / or simultaneously with other steps. Also, not all operations, steps and / or features need to be performed to achieve an embodiment of the invention. Moreover, each operation or step described herein may include multiple sub-steps or actions.

[0030] Some embodiments of the present disclosure provide a two-layer composite hydrogel microcarrier including an inner layer gel structure and an outer layer gel structure. The inner layer gel structure is obtained by ionically crosslinking the inner layer polymer with the inner layer crosslinker. The outer layer gel structure is obtained by covalently crosslinking the outer layer monomer with the outer layer crosslinker, and covers the inner layer gel structure.

[0031] The inner layer gel structure of the two-layer composite hydrogel microcarrier is an ion-crosslinked structure, and has limitations such as the structure being easily affected by the pH value of the environment, or the structure being collapsed due to the weakening of the ionic force caused by water absorption and expansion. The covalently bonded outer layer gel structure in the present disclosure can provide physical support for the inner layer gel structure, avoiding the problem of the inner layer gel structure becoming unstable, and improving the structural strength of the two-layer composite hydrogel microcarrier. In addition, the outer layer gel structure can be made into a barrier layer, which can further delay the release time of the loaded contents (e.g., nutrient molecules), reduce the burst release phenomenon, and stably release the loaded contents for a long period of time.

[0032] In some embodiments, the outer layer gel structure is in the form of a porous membrane, which covers the inner layer gel structure so as to encase the inner layer gel structure, has a thickness smaller than that of the inner layer gel structure, and there are van der Waals forces between the outer layer gel structure and the inner layer gel structure that attract each other, but there is no covalent bond between them.

[0033] In some embodiments, the inner layer gel structure is a plurality of inner layer sheet-like structures connected to each other and separated from each other by a plurality of inner layer holes, and the outer layer gel structure is a plurality of outer layer sheet-like structures connected to each other and separated from each other by a plurality of outer layer holes having a pore size smaller than the pore size of each inner layer hole. The difference in pore size between the inner layer gel structure and the outer layer gel structure can provide the outer layer gel structure with good structural strength, and the small pore size design of the outer layer gel structure can provide the two-layer composite hydrogel microcarrier with good sustained content release effect.

[0034] In some embodiments, in a cross-sectional view, each inner layer sheet-like structure (or outer layer sheet-like structure) has an arc shape, and the inner layer hole (or outer layer hole) is defined by the concave surface between them. In some embodiments, the diameter of the inner layer hole represents the longest vertical distance between the two inner layer sheet-like structures located on both sides of the inner layer hole. The diameter of the outer layer hole represents the longest vertical distance between the two outer layer sheet-like structures located on both sides of the outer layer hole. In some embodiments, the diameter of the inner layer hole is 250 microns to 1000 microns, for example, 250 microns, 500 microns, 750 microns, 1000 microns, or a value within the aforementioned interval. In some embodiments, the diameter of the outer layer hole is 50 microns to 500 microns, for example, 50 microns, 100 microns, 150 microns, 200 microns, 250 microns, 300 microns, 350 microns, 400 microns, 450 microns, 500 microns, or a value within the aforementioned interval. If the pore size is too large, the structure becomes unstable and the content release rate is too fast, making it impossible to achieve sustained release, whereas if the pore size is too small, the supported content is blocked excessively, making it difficult to achieve stable and long-term release of the content.

[0035] In some embodiments, the thickness of the outer gel structure is between 25 microns and 1000 microns, for example, 25 microns, 50 microns, 100 microns, 200 microns, 300 microns, 400 microns, 500 microns, 600 microns, 700 microns, 800 microns, 900 microns, 1000 microns, or a value within the aforementioned range. If the thickness is too thick, the release rate of the supported contents is too slow, and if the thickness is too thin, the release rate of the supported contents is too fast and the structural strength is insufficient. It can be understood that the release of the contents (e.g., lipophilic small molecules (molecular weight less than 500 grams / mole, solubility in non-polar solvents greater than 0.1 micrograms / gram) or polymeric proteins (molecular weight greater than at least 500 grams / mole)) can be delayed with an increase in thickness.

[0036] In some embodiments, the inner layer polymer comprises a first inner layer polymer and a second inner layer polymer, and the inner layer gel structure is an interpenetrating structure between the first inner layer polymer and the second inner layer polymer (i.e., the polymer chains of the first inner layer polymer and the second inner layer polymer cross each other), and the design of the interpenetrating structure can provide good support and stabilize the structural strength of the inner layer gel structure.

[0037] In some embodiments, the inner layer polymer and the inner layer crosslinked product have opposite electrical properties, for example, the inner layer polymer is negatively charged and the inner layer crosslinked product is positively charged, and the inner layer crosslinked product and the inner layer polymer are crosslinked by ionic bonds formed between positive and negative charges to form an inner layer gel structure, or the inner layer polymer is positively charged and the inner layer crosslinked product is negatively charged. When the inner layer polymer has different dissociation degrees at different pH values, the inner layer gel structure crosslinked by ionic bonds has pH sensitivity, and the strength of the ionic bonds changes with the change in pH value, thereby changing the inner layer gel structure.

[0038] In some embodiments, when the first inner layer polymer is sodium alginate (SA), the second inner layer polymer is carboxymethyl cellulose (CMC). The selection and use of sodium alginate and carboxymethyl cellulose has the advantages of easy storage and preparation, safety and non-toxicity, gel formation at room temperature, and easy absorption by the human body. In addition, compared with the use of sodium alginate alone, the combination of sodium alginate and carboxymethyl cellulose can improve the viscosity and structural strength of the inner layer gel structure, and the pore size of the inner layer pores can be adjusted by adjusting the blending ratio of sodium alginate and carboxymethyl cellulose, providing greater flexibility in selecting the inner layer gel structure. In addition, when sodium alginate and carboxymethyl cellulose are selected and used, the inner layer gel structure formed by the inner layer gel structure is relatively dense because sodium alginate and carboxymethyl cellulose have carboxy groups and are not easily liberated in an acidic environment, and the inner layer gel structure is relatively loose because of high liberation in a basic environment.

[0039] In some embodiments, the weight percentage of sodium alginate, relative to the weight percentage of the inner layer gel structure taken as 100%, is 0.1% to 5%, e.g., 0.1%, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, 4.75%, 5%, or any interval therebetween. The weight percentage of carboxymethylcellulose is 0.1% to 5%, for example, 0.1%, 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, 4.75%, 5%, or a value within the aforementioned interval. If both are too high, the inner gel structure becomes too dense and the release efficiency of the inner gel structure is limited, and if both are too low, the colloidal structure becomes loose and unstable, or no gel can be formed. Furthermore, as the weight percentage of sodium alginate increases and the weight percentage of carboxymethylcellulose decreases, the pore size of the inner layer pores increases, improving the expansion rate of the inner layer gel structure when it absorbs water and the release efficiency of the contents. Conversely, as the weight percentage of sodium alginate decreases and the weight percentage of carboxymethylcellulose increases, the pore size of the inner layer pores decreases, decreasing the expansion rate and release efficiency of the inner layer gel structure (e.g., reducing the release of high molecular weight proteins).

[0040] In some embodiments, when the first inner layer polymer is a poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer, the second inner layer polymer is a derivative of poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acyl group. In one embodiment, the poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer includes an ABA triblock copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) (Tri-PCG), and the acyl group is an acrylate group, so that the derivative of the poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acyl group is a poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acrylate group (Tri-PCG-acryl). In addition, the inner layer gel structure using Tri-PCG and Tri-PCG-acryl selectively changes colloidal properties in response to temperature changes within the applicable temperature range of the human body (e.g., transforms from solution to colloid at 25°C to 37°C), and can change the viscosity and release ability of the inner layer gel structure, and the structure is relatively stable and not easily collapsed. In some embodiments, the bilayer composite hydrogel microcarrier further includes an inner layer auxiliary molecule (e.g., dipentaerythritol hexakis(3-mercaptopropionate; DPMP) present in the inner layer gel structure, and as the temperature gradually increases, DPMP can form a covalent bond structure with Tri-PCG-acryl to strengthen the colloidal properties and improve the temperature sensitivity of the inner layer gel structure.

[0041] In some embodiments, the weight percentage of the inner gel structure is 100%, and the sum of the weight percentages of Tri-PCG and Tri-PCG-acryl is 15% to 30%, such as 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or any value within the aforementioned intervals. If the weight percentage is too high, the inner gel structure will be too dense and the release efficiency of the inner gel structure will be limited, and if the weight percentage is too low, the colloidal structure will be loose and unstable, or no gel will be formed.

[0042] In some embodiments, when the inner layer polymer is negatively charged, the inner layer crosslinked product contains calcium ions (Ca 2+ Compared to other cross-linked inner layers, calcium ions have the advantages of easy availability, low cost, and low environmental hazard.

[0043] In some embodiments, the outer layer monomer comprises N,N-dimethylacrylamide (DMAA), acrylamide (AA), or a combination thereof. When DMAA is selected for use instead of AA, the pore size of the outer layer pores of the formed outer layer gel structure is relatively large, the release rate of the loaded contents is relatively high (e.g., the release rate of high molecular weight proteins is improved), and the two-layer composite hydrogel microcarrier has a large swelling rate when absorbing water.

[0044] In some embodiments, the outer layer crosslinker comprises N,N'-Methylene-Bis-Acrylamide (BIS), which can form a covalent bond with DMAA or AA to crosslink DMAA to poly(N,N-dimethylacrylamide) (PDMA) or crosslink AA to poly(acrylamide) (PAA).

[0045] Some embodiments of the present disclosure provide a method for producing a bilayer composite hydrogel microcarrier, comprising the steps of: providing an inner layer polymer and an inner layer crosslinked product; mixing the inner layer polymer and the inner layer crosslinked product to obtain an inner layer gel structure by ionic crosslinking from the inner layer polymer and the inner layer crosslinked product; providing an outer layer monomer and an outer layer crosslinked product; mixing the inner layer gel structure, the outer layer monomer and the outer layer crosslinked product to obtain an outer layer gel structure by covalent crosslinking polymerization from the outer layer monomer and the outer layer crosslinked product, and the outer layer gel structure covers the inner layer gel structure to obtain a bilayer composite hydrogel microcarrier. By mixing the inner layer gel structure, the outer layer monomer and the outer layer crosslinked product, an outer layer gel structure covering the inner layer gel structure can be formed, and the outer layer gel structure can provide physical support for the inner layer gel structure, improve the structural strength of the bilayer composite hydrogel microcarrier, delay the release time of the loaded contents, and realize long-term stable release.

[0046] In some embodiments, the step of providing an inner layer polymer and an inner layer crosslinked product includes providing a first inner layer polymer, a second inner layer polymer, and an inner layer crosslinked product.

[0047] In some embodiments, the first inner layer polymer is sodium alginate (SA) and the second inner layer polymer is carboxymethylcellulose (CMC), which has the advantages of being easy to store and prepare, safe and non-toxic, capable of forming a gel at room temperature, and easily absorbed by the human body.

[0048] In some embodiments, when the first inner layer polymer is a poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer, the second inner layer polymer is a derivative of a poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acyl group. In one embodiment, the poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer is an ABA triblock copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) (Tri-PCG), and the derivative of the poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acyl group is a poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acrylate group (Tri-PCG-acryl). The inner gel structure made of Tri-PCG and Tri-PCG-acryl is relatively dense, and within the applicable temperature range of the human body, it can change its colloidal properties according to changes in temperature (for example, it changes from a solution to a colloid at 25°C to 37°C), and the viscosity and release capacity of the inner gel structure can be changed, and the structure is relatively stable and not easily collapsed.

[0049] In some embodiments, the inner layer polymer and the inner layer crosslinked material have opposite electrical properties, ie, when the inner layer polymer is negatively charged, the inner layer crosslinked material contains calcium ions.

[0050] In some embodiments, the step of mixing the inner layer polymer and the inner layer crosslinked product includes mixing the first inner layer polymer, the second inner layer polymer, the inner layer crosslinked product, a radical generator, and water. By adding the radical generator in this step, the radical generator stored in the inner layer gel structure diffuses into the outer layer when the outer layer monomer, the outer layer crosslinked product, and the catalyst are subsequently added, and reacts with the outer layer monomer, the outer layer crosslinked product, and the catalyst to initiate a reaction to form an outer layer gel structure in the outer layer. Therefore, by adding the radical generator in this step, it is possible to avoid a premature reaction when the radical generator is added simultaneously with the outer layer monomer, the outer layer crosslinked product, and the catalyst, or a situation in which the outer layer gel structure does not adequately cover the inner layer gel structure.

[0051] In some embodiments, the weight ratio of the first inner layer polymer to the second inner layer polymer is 1:5 to 5:1, e.g., 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or any interval therebetween. If the first inner layer polymer has more releasable negatively charged groups (e.g., carboxy groups) in a basic environment versus an acidic environment, the swelling rate of the inner layer gel structure will increase with increasing weight ratio.

[0052] In some embodiments, the step of mixing the inner layer polymer and the inner layer crosslinked material includes mixing a first inner layer polymer, a second inner layer polymer, an inner layer crosslinked material, a radical generator, and water.

[0053] In some embodiments, when the total weight percentage of the first inner layer polymer, the second inner layer polymer, the inner layer crosslinked product, the radical generator, and the water is 100%, the weight percentage of sodium alginate is 0.1% to 5%, and the weight percentage of carboxymethylcellulose is 0.1% to 5%. If the weight percentage is too high, the inner gel structure becomes too dense, and the release efficiency of the inner gel structure is limited; if the weight percentage is too low, the colloidal structure is loose and unstable, or no gel can be formed; if the weight percentage of carboxymethylcellulose is greater than 1% (e.g., 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75%, 3%, 3.25%, 3.5%, 3.75%, 4%, 4.25%, 4.5%, 4.75%, 5%, or any value within the aforementioned interval), the bilayer composite hydrogel microcarrier can be endowed with sufficient structural strength to continuously culture stem cells for several days without collapse. In some embodiments, when the weight ratio of sodium alginate and carboxymethylcellulose is 3:2, the pore size of the inner gel structure can be controlled to stably release nutrients at an appropriate rate, thereby ensuring that stem cells steadily take in nutrients, and improving the growth rate of stem cells.

[0054] In some embodiments, the total weight percentage of the poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer and the derivative of poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acyl group is 15%-30% when the total weight percentage of the first inner layer polymer, the second inner layer polymer, the inner layer crosslinker, the radical generator and the water is 100%. If the weight percentage is too high, the inner layer gel structure is too dense and the release efficiency of the inner layer gel structure is limited, and if the weight percentage is too low, the colloidal structure is loose and unstable or no gel can be formed.

[0055] In some embodiments, the step of mixing the first inner layer polymer, the second inner layer polymer, the inner layer crosslinker, the radical generator, and the water further comprises adding dipentaerythritol hexakis(3-mercaptopropionate), bovine serum albumin, or a combination thereof. In some embodiments, the step of mixing the first inner layer polymer, the second inner layer polymer, the inner layer crosslinker, the radical generator, and water comprises mixing a first solution, a second solution, calcium ions, and ammonium sulfate, where the first solution comprises poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer or poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer and dipentaerythritol hexakis(3-mercaptopropionate) (DPMP), and the second solution comprises a derivative of poly(ε-caprolactone-co-glycolic acid)·poly(ethylene glycol) copolymer having an acyl group and bovine fetal serum albumin.

[0056] As the temperature increases, DPMP tends to form a covalent bond with the acyl group, which improves the density of the inner layer gel structure, so it is understood that adding DPMP can improve the sustained release ability of the inner layer gel structure when the temperature increases, which is advantageous for application to the human body. In some embodiments, the weight percentage of the first solution is 100%, and the weight percentage of DPMP is 5% to 15%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a value within the above-mentioned range. In addition, by adding bovine fetal serum albumin, bovine fetal serum albumin can be coated in the bilayer composite hydrogel microcarrier, and when the bilayer composite hydrogel microcarrier is used for cell culture, bovine fetal serum albumin can be released continuously to provide a cell nutrient source for a long period of time.

[0057] In some embodiments, the step of mixing the inner layer gel structure, the outer layer monomer, and the outer layer crosslinked material includes mixing the inner layer gel structure, N,N-dimethylacrylamide (DMAA), N,N'-methylenebisacrylamide (BIS), and a catalyst, or mixing the inner layer gel structure, acrylamide (AA), N,N'-methylenebisacrylamide, and a catalyst. The BIS and DMAA or AA form a covalent outer layer gel structure, which improves the physical support of the inner layer gel structure and forms denser pores than the inner layer gel structure, thereby extending the release of the loaded contents.

[0058] In some embodiments, the weight percentage of the inner layer gel structure is 50% to 80% (e.g., 50%, 60%, 70%, 80% or a value within the aforementioned interval), the weight percentage of the outer layer monomer is 15% to 40% (e.g., 15%, 20%, 25%, 30%, 35%, 40% or a value within the aforementioned interval), and the weight percentage of the outer layer crosslinked product is 5% to 10% (e.g., 5%, 6%, 7%, 8%, 9%, 10% or a value within the aforementioned interval), assuming that the total weight percentage of the inner layer gel structure, the outer layer monomer, and the outer layer crosslinked product is 100%. If the weight percentage of the inner layer gel structure or the outer layer gel structure is too low, it is difficult to form a bilayer composite hydrogel microcarrier. If the weight percentage of the inner layer gel structure or the outer layer gel structure is too high, the release rate of the contents supported in the bilayer composite hydrogel microcarrier is too low.

[0059] In some embodiments, the weight ratio of the inner layer gel structure to the outer layer monomer is 5:4 to 16:3 (e.g., 5:4, 5:3, 2:1, 8:3, 10:3, 4:1, 16:3, or a value within the aforementioned interval). If the weight ratio is too high, the structure of the bilayer composite hydrogel microcarrier will be unstable, and if the weight ratio is too low, the outer layer of the bilayer composite hydrogel microcarrier will be too thick, and the release rate of the loaded contents will be too low.

[0060] In some embodiments, in the step of mixing the inner layer gel structure, the outer layer monomer, and the outer layer crosslinked product, the mixing time is 0.5 to 5 minutes, for example, 0.5 minutes, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, or a value within the aforementioned interval. By controlling the mixing time, the thickness of the outer layer gel structure can be controlled, and the structural strength and release rate of the two-layer composite hydrogel microcarrier can be controlled.

[0061] Some embodiments of the present disclosure further provide a method for culturing stem cells using the aforementioned bi-layer composite hydrogel microcarriers, comprising the steps of providing stem cells, bi-layer composite hydrogel microcarriers, and nutritional components; mixing the stem cells, bi-layer composite hydrogel microcarriers, and nutritional components to obtain a gelling medium; and adding a culture medium to the gelling medium. The two-layer composite hydrogel microcarrier includes an inner layer gel structure and an outer layer gel structure, the inner layer gel structure is obtained by ionically crosslinking the inner layer polymer with the inner layer crosslinker, the inner layer polymer includes a first inner layer polymer and a second inner layer polymer, the first inner layer polymer is sodium alginate, the second inner layer polymer is carboxymethylcellulose, the weight ratio of sodium alginate to carboxymethylcellulose is 3:2, the weight percentage of the inner layer gel structure is 100%, the weight percentage of carboxymethylcellulose is greater than 1%, the outer layer gel structure is obtained by covalently crosslinking the outer layer monomer with the outer layer crosslinker, the inner layer gel structure is covered, and the nutritional component is located inside the inner layer gel structure. By controlling the weight percentage of carboxymethylcellulose, it is possible to impart good structural stability to the two-layer composite hydrogel microcarrier, and by defining the weight ratio of sodium alginate to carboxymethylcellulose and the position of the nutritional component, it is possible to extend the release time of the loaded nutritional component. Therefore, when culturing stem cells using a two-layer composite hydrogel microcarrier, it can be maintained for a long time until it collapses, the amount of stem cells cultured per unit area can be increased, burst release of contents can be avoided, the contents can be released continuously to the stem cells, the stem cell culture time and the number of times nutrients are added can be increased, and the culture flow can be simplified.

[0062] In some embodiments, the stem cells include embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or combinations thereof.

[0063] It is understood that according to different characteristics of stem cells, bilayer composite hydrogel microcarriers with different structural strength and release rate can be selected and used.For example, when culturing adipose stem cells with fast growth rate, sodium alginate and carboxymethylcellulose with large inner pore size can be selected and used, and when culturing neural stem cells with slow growth rate, Tri-PCG and Tri-PCG-acryl with small inner pore size can be selected and used.

[0064] In order to further illustrate the two-layer composite hydrogel microcarrier, the method for producing the two-layer composite hydrogel microcarrier and the method for culturing stem cells provided by the embodiments of the present disclosure, the following examples are provided. Please note that the following examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0065] Example 1: Preparation method of double-layer composite hydrogel microcarrier

[0066] 1. Inner layer gel structure

[0067] Below, the corresponding processes for different inner layer polymers are provided.

[0068] 1.1 Sodium alginate and carboxymethylcellulose

[0069] Sodium alginate (SA) and carboxymethylcellulose (CMC) were mixed in different weight ratios (SA:CMC=4:1, 2:3, 3:2, 1:4), then injected into 5% calcium chloride (CaCl2) solution containing 1.5% ammonium persulfate (APS) to form a mixed solution, which was stirred for 20 minutes to crosslink SA and CMC with calcium ions to form multiple groups of inner layer gel structures with different concentrations of SA and CMC, and inner layer hydrogels were obtained. The SA and CMC in each group were 2.0% / 0.5%, 1.0% / 1.5%, 1.5% / 1.0%, 0.5% / 2.0%, respectively, the reaction concentration of APS was 1%, and the reaction concentration of calcium ions was 4%.

[0070] It is understood that in the process of forming the mixed solution (not limited to the example of using sodium alginate and carboxymethylcellulose as the inner layer polymer), depending on the subsequent stem cell culture requirements, culture medium can be added or nutritional components (e.g., growth factors) can be added to the mixed solution to make the final concentration of the nutritional components 5 milligrams / milliliter to 10 milligrams / milliliter, in preparation for future clinical application.

[0071] 1.2 ABA-type triblock copolymer of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) (Tri-PCG) and its acrylate-containing Tri-PCG derivative (also called Tri-PCG-acryl)

[0072] 1.2.1 Preparation of Tri-PCG

[0073] Poly(ethylene glycol) (PEG) (15.0 g, 10 mmol) was dried under reduced pressure at 120° C. for 3 hours. ε-caprolactone (33.3 g, 291 mmol), glycolide (5.87 g, 50.6 mmol) and tin 2-ethylhexanoate (Sn(Oct)2) (149 mg, 367 μmol) as a catalyst were added to the flask containing PEG to obtain a reaction solution.

[0074] The reaction solution was then frozen with liquid nitrogen and dried under reduced pressure to obtain a reaction product. The flask containing the reaction product was then immersed in an oil bath at 160°C for 12 hours to carry out a ring-opening polymerization reaction. The reaction product was then dissolved in 100 milliliters of chloroform and precipitated with 1000 milliliters of diethyl ether, and the dissolution and precipitation steps were repeated three times. The supernatant was then removed, and the precipitate was treated by drying under reduced pressure to obtain Tri-PCG, a white solid.

[0075] 1.2.2 Preparation of Tri-PCG-acryl

[0076] Acrylic acid (2.0 ml, 29.2 mmol) was dissolved in 250 ml of dichloromethane (CHCl) to obtain an acrylic acid solution, and N,N'-dicyclohexyl carbodiimide (DCC) (6.24 g, 30.2 mmol) was dissolved in 250 ml of dichloromethane to obtain an N,N'-dicyclohexyl carbodiimide solution. Then, in an ice bath, the N,N'-dicyclohexyl carbodiimide solution was added to the acrylic acid solution and stirred for 1 hour, and the volume ratio of the N,N'-dicyclohexyl carbodiimide solution to the acrylic acid solution was 1:1. Next, Tri-PCG (20.3 g, 5.1 mmol) and 4-dimethylaminopyridine (DMAP) (299.5 mg, 2.5 mmol) dissolved in 250 mL of dichloromethane were added to the mixed solution containing acrylic acid and N,N'-dicyclohexylcarbodiimide, and the mixture was stirred at 25°C for 24 hours. The by-product dicyclohexylurea was then removed by filtration. After dichloromethane evaporated, chloroform was used as a good solvent (a solvent with high dissolving power for solutes and an interaction parameter with polymer solutes smaller than 0.5) to extend the polymer long chains in the solution, and a mixture of n-hexane and ethanol (volume ratio of n-hexane to ethanol is 8 / 2) was used as a poor solvent (a solvent with low dissolving power for solutes and an interaction parameter with polymer solutes close to or larger than 0.5) to perform reprecipitation three times. Subsequently, Tri-PCG-acryl, a yellowish white solid, was obtained by drying under reduced pressure.

[0077] 1.2.3. Preparation of Tri-PCG aqueous solution, Tri-PCG-acryl aqueous solution, and Tri-PCG / DPMP aqueous solution

[0078] Regarding the Tri-PCG aqueous solution, first, Tri-PCG (246.5 milligrams) was dissolved in 986 microliters of adipose stem cell culture medium (product name: StemPro) containing 10% fetal bovine serum. TM MSC SFM, Product Number: Gibco TM A1033201). After immersing in a water bath at about 90°C for 5 seconds, it was cooled at room temperature with continuous stirring, and the immersion and cooling steps were repeated three times. It was then cooled under water bath conditions (20°C to 25°C), sonicated for 30 minutes to remove air bubbles, and the pH value was adjusted to 7.4 with sodium hydroxide and adipose stem cell culture medium to obtain a 20% Tri-PCG aqueous solution (which can be replaced with the subsequent Tri-PCG / DPMP aqueous solution depending on the colloid requirements).

[0079] For the Tri-PCG-acryl aqueous solution, Tri-PCG-acryl (165 milligrams) was dissolved in adipose stem cell culture medium (660 microliters) containing 10% fetal bovine serum and stirred overnight at 4° C. Then, the mixture was sonicated for 30 minutes at low temperature (20° C. to 25° C.) to remove air bubbles, and the pH value was adjusted to 7.4 with sodium hydroxide and adipose stem cell culture medium to obtain a 20% Tri-PCG-acryl aqueous solution.

[0080] For the Tri-PCG / DPMP aqueous solution, dipentaerythritol hexakis(3-mercaptopropionate; DPMP) (90.4 milligrams) was dissolved in 1 milliliter of acetone to obtain a DPMP solution. The DPMP solution was added to a sample tube containing 750 milligrams of Tri-PCG, and a mixed solution was obtained after refilling with 7 milliliters of acetone. The mixed solution was added to 63 milliliters of water, stirred and sonicated for 30 minutes, followed by removing acetone and lyophilization to obtain a Tri-PCG / DPMP mixture (DPMP accounts for approximately 10.8% in the Tri-PCG / DPMP mixture).

[0081] The Tri-PCG / DPMP mixture was then dissolved in adipose stem cell culture medium (354 microliters) containing 10% fetal bovine serum. After immersion in a water bath at approximately 90°C for 5 seconds, it was continuously stirred and cooled at room temperature, and the immersion and cooling steps were repeated three times. The mixture was then ultrasonicated for 30 minutes under low temperature conditions (20°C to 25°C) to remove air bubbles, and the pH value was adjusted to 7.4 with sodium hydroxide and adipose stem cell culture medium to obtain a 20% Tri-PCG / DPMP aqueous solution.

[0082] 1.2.4 Preparation of the inner layer hydrogel

[0083] After mixing the Tri-PCG / DPMP aqueous solution and the Tri-PCG-acryl aqueous solution in an appropriate ratio, the mixture is poured into a 5% calcium chloride (CaCl2) aqueous solution containing 1.5% ammonium persulfate (APS) to form a mixed solution, which is stirred for 20 minutes, and the Tri-PCG and Tri-PCG-acryl are cross-linked by calcium ions to form an inner layer gel structure, to obtain an inner layer hydrogel, in which the reaction concentrations of Tri-PCG / DPMP and Tri-PCG-acryl are 70%-79% and 16%-25% respectively, the reaction concentration of APS is 1%, the reaction concentration of calcium ions is 4%, and the total weight percentage of the inner layer gel structure Tri-PCG and Tri-PCG-acryl is 16%-33%, thereby ensuring that the inner layer hydrogel is in a colloidal state in the working temperature range.

[0084] As the temperature increases, the acrylate groups of Tri-PCG and Tri-PCG-acryl, or DPMP and Tri-PCG-acryl, can form covalent bonds and change the gel morphology, so the intimal gel structure prepared using Tri-PCG-acryl and Tri-PCG / DPMP, or Tri-PCG-acryl and Tri-PCG, has temperature sensitivity.

[0085] For example, see FIG. 1, which shows the gel state change diagram at different concentrations of Tri-PCG and temperatures (Tri-PCG in this example is stored in phosphate buffered saline (PBS)), which shows that by adjusting the concentration of Tri-PCG (e.g., corresponding to the sum of the concentrations of Tri-PCG / DPMP and Tri-PCG-acryl in this example) or temperature, the gel state can be changed, and the viscosity and release capacity of the gel can be adjusted according to the change in the gel state.

[0086] In another example, a Tri-PCG aqueous solution may be used instead of a Tri-PCG / DPMP aqueous solution and mixed with Tri-PCG-acryl. Compared to a Tri-PCG aqueous solution, a Tri-PCG / DPMP aqueous solution contains DPMP that can form a covalent bond with Tri-PCG-acryl when heated, so it is understood that the intimal gel structure prepared using a Tri-PCG / DPMP aqueous solution has good temperature sensitivity.

[0087] It is understood that the inner layer gel structure prepared by "1.1, sodium alginate and carboxymethylcellulose" and the inner layer gel structure prepared by "1.2 ABA type triblock copolymer (Tri-PCG) of poly(ε-caprolactone-co-glycolic acid) and poly(ethylene glycol) and Tri-PCG derivative having acrylate group (also called Tri-PCG-acryl)" are different in that the inner layer gel structure using Tri-PCG / DPMP and Tri-PCG-acryl is relatively stable and not easily collapsed, but the preparation process is complicated and requires the use of organic solvents. The inner layer gel structure using SA and CMC has the advantages of a simple preparation process and high environmental friendliness, but has the limitation that the structure is also affected by the pH value.

[0088] Therefore, depending on the growth characteristics of the stem cells to be cultured later, appropriate components can be selected and used to prepare the inner layer gel structure; for example, SA and CMC, which are easy to prepare, are selected and used to culture adipose stem cells, which have a relatively fast growth rate, and Tri-PCG / DPMP and Tri-PCG-acryl, which have relatively high structural strength, are selected and used to culture neural stem cells, which have a relatively slow growth rate.

[0089] 2. Outer-layer gel structure and two-layer composite hydrogel microcarriers

[0090] Next, N,N-dimethylacrylamide (DMAA) or acrylamide (AA) as the outer layer monomer, N,N'-methylenebisacrylamide (BIS) as the outer layer crosslinker, and tetramethylethylenediamine (TEMED) as the catalyst were mixed, and then the inner layer hydrogel prepared previously (here, the inner layer hydrogel obtained by "1.1, sodium alginate and carboxymethylcellulose" was selected and used) was added and mixed for different times, and DMAA or AA and BIS were crosslinked to form poly(N,N-dimethylacrylamide) (PDMA) or poly(acrylamide) (PAA), and two-layer composite hydrogel microcarriers with different thicknesses of the outer layer gel structure or different outer layer components were obtained, and the reaction concentration of DMAA or AA was 1 mol / L, the reaction concentration of BIS was 2.2 mol / L, and the reaction concentration of TEMED was 15 milligrams / milliliter.

[0091] Specifically, during the mixing process, APS in the inner hydrogel diffused outward and provided radicals to initiate the reaction that formed the outer gel structure. The outer monomers were covalently bonded to BIS and PDMA or PAA by the APS radicals and TEMED catalyst to form the outer gel structure.

[0092] Finally, unreacted outer layer monomer was removed by stirring and washing with water.

[0093] Example 2: Stem cell culture method using bilayer composite hydrogel microcarriers

[0094] First, 1x10 7 An adipose stem cell suspension (i.e., adipose stem cells suspended in adipose stem cell culture medium) containing 100000000000 particles / milliliter and a two-layer composite hydrogel microcarrier were mixed in a volume ratio of 1:1 to form a stem cell mixed gel, and allowed to stand at 37°C for 30 minutes to improve the degree of gelation.

[0095] Next, 400 microliters of adipose stem cell culture medium was dropped onto the surface of the stem cell mixed gel, and then cultured in an environment containing 37°C and 5% carbon dioxide. Every two days, 200 microliters of adipose stem cell culture medium (supernatant) was removed and replaced with fresh adipose stem cell culture medium. After culturing until the bilayer composite hydrogel microcarrier burst, the adipose stem cells were collected with PBS and other culture components were removed.

[0096] It is understood that the provision of an outer gel layer provides physical stability to the inner gel layer, preventing the inner gel layer from swelling and bursting due to water absorption or structural collapse in the presence of alkali, while preventing excessive release and leakage of nutritional components, and maintaining a stable release of nutritional components.

[0097] Example 3, Efficacy Test

[0098] First, a two-layer composite hydrogel microcarrier was prepared according to the method of Example 1 described above, and the specific components, weight percentages and formation time of the outer layer gel structure (i.e., the mixing time in "2. Outer layer gel structure and two-layer composite hydrogel microcarrier") were adjusted, and the differences in structural properties and content release efficiency between different two-layer composite hydrogel microcarriers were compared, and the conditions of each group are exemplified as follows:

[0099] [Table 1]

[0100] 1. Gel morphology under electron microscope

[0101] First, the bilayer composite hydrogel microcarriers of each group were observed under different magnifications by scanning electron microscope, and the results are shown in Figure 2, where a-c in the top row are the SA-CMC@PDMA-1 group, d-f in the second row are the SA-CMC@PDMA-3 group, and g-i in the bottom row are the SA-CMC@PAA-1 group.

[0102] As can be seen from Figure 2, the inner and outer layers of the two-layer composite hydrogel microcarrier are connected to each other in a sheet-like structure, the sheet structures are spaced apart by three-dimensional pores, and the boundaries between the inner and outer layers are clearly visible. In addition, the pore sizes of the inner and outer gel structures are different, and the pore size of the outer gel structure is smaller than that of the inner gel structure.

[0103] In addition, by comparing Figure c (SA-CMC@PDMA-1 group) and Figure f (SA-CMC@PDMA-3 group), it was found that the thickness of the outer layer gel structure increased from about 100 microns to about 450 microns when the crosslinking time of the outer layer increased from 1 min to 3 min.

[0104] Moreover, by comparing Figure b (SA-CMC@PDMA-1 group) and Figure e (SA-CMC@PDMA-3 group), it was found that with the decrease in the concentration of SA, a significant change was observed in the pore size of the inner and outer layers of the pores, and the higher the proportion of SA, the larger the pore size of the inner layer pores.

[0105] As can be seen from Fig. 2, the bilayer composite hydrogel microcarrier has a bilayer skeleton structure, the pore size of the inner gel structure is relatively large, which is favorable for the adsorption of nutritional components, and the outer gel structure is relatively dense, which provides physical support for the inner gel structure, and can avoid the collapse of the inner gel structure and the excessive release of nutritional components. Therefore, the bilayer composite hydrogel microcarrier can provide a scaffold for the three-dimensional growth of stem cells to retain nutritional components for a long time, increase the number of stem cells cultured, and extend the time for which they can be cultured sustainably. The relevant effectiveness will be further verified below.

[0106] 2. Water absorption and expansion

[0107] In order to detect the water absorption and swelling of the single inner layer gel structure (single layer gel) and the two-layer composite hydrogel microcarrier, the inner layer gel structure (four groups, the SA concentration and CMC concentration of each group are 0.5% SA / 2.0% CMC, 1.0% SA / 1.5% CMC, 1.5% SA / 1.0% CMC, 2.0% SA / 0.5% CMC) and the two-layer composite hydrogel microcarrier (SA-CMC@PDMA-1 group, SA-CMC@PDMA-2 group, SA-CMC@PDMA-3 group, SA-CMC@PAA-1 group) are naturally air-dried, and the inner layer gel structure and the two-layer composite hydrogel microcarrier after air-drying (hereinafter referred to as samples) are appropriately weighed and subjected to the swelling test, the flow of which is as follows:

[0108] First, the sample was placed in an acidic solution (0.5 M hydrochloric acid) with a pH value of 1.2 for 2 hours, and then transferred to a basic solution (1 M trihydroxymethylaminomethane) with a pH value of 7.4 until the weight reached equilibrium or decreased (representing the beginning of dissolution). During this process, the sample was taken out of the solution every 30 minutes and weighed after removing the residual solution, and the swelling ratio (SR) at each time point was calculated using the following formula:

[0109] SR = [(m0-mt) / m0]

[0110] SR is the swelling ratio of the bilayer composite hydrogel microcarrier, mt is the mass of the bilayer composite hydrogel microcarrier at time t (swollen state), and m0 is the initial mass of the hydrogel.

[0111] See FIG. 3A for the swelling rate trends of the inner-layer gel structures obtained from the above tests, and see FIG. 3B for the swelling rate trends of the two-layer composite hydrogel microcarriers.

[0112] Figure 3A shows the water absorption and expansion properties of different inner layer gel structures. The reason why the expansion rate of the four types of inner layer gel structures is low in an acidic environment is that SA and CMC have many carboxyl groups (-COOH), but in an acidic solution, the carboxyl groups are not liberated, the electrostatic repulsion between polymers is low, the gel network structure is dense, and the hydrophilicity of SA and CMC is reduced. Therefore, the expansion rate of the inner layer gel structure (single layer gel) is lower in an acidic solution compared to a basic solution. It was also observed that the expansion rate decreased as the concentration of CMC decreased in an acidic solution.

[0113] In contrast, in a basic environment, the swelling rate increased over time, then gradually increased and then decreased. - ), which forms electrostatic repulsion between the carboxyl groups and increases with time. The repulsion gradually increases, and the monolayer gel expands and expands the network gap, changes in structure, increases in hydrophilicity, absorbs water molecules, and improves the expansion rate. In the later stage of the action, with the change in structure, the ionic bridge formed by the carboxyl groups and calcium ions gradually becomes unstable, the concentration of the carboxyl groups decreases, and the crosslinking reaction between the carboxyl groups and calcium ions becomes weaker, causing the monolayer gel to gradually collapse.

[0114] Figure 3B shows the water absorption and swelling characteristics of the two-layer composite hydrogel microcarriers with different gel structures. Compared with the water absorption and swelling time (time to absorb water before collapse) of the single-layer gel (only the inner layer gel structure) in Figure 3A being 4.5 hours, Figure 3B shows that the water absorption and swelling time of the two-layer composite hydrogel microcarriers is obviously extended to 12 hours, and the overall swelling rate is higher than that of the single-layer gel. That is, the inner layer gel structure of the two-layer composite hydrogel microcarriers is sensitive to pH value, but the outer layer gel structure is not sensitive to pH value, so that even in a basic environment, the outer layer gel structure can maintain the integrity of the gel structure and is not easily collapsed.

[0115] In addition, when comparing the SA-CMC@PDMA-2 group (outer layer crosslinking time was 2 h) and the SA-CMC@PDMA-3 group (outer layer crosslinking time was 3 h), it was found that the collapse of the gel could be delayed by extending the outer layer crosslinking time to increase the thickness of the outer layer gel structure.

[0116] Comparing SA-CMC@PDMA-1 group (1.5% SA / 1.0% CMC) and SA-CMC@PDMA-2 group (0.5% SA / 2.0% CMC), it was found that the group with lower SA concentration had a relatively lower swelling rate after 4 hours. Therefore, lowering the concentration of SA in a basic environment can be a way to extend the release time of nutrients.

[0117] Finally, when comparing the SACMC@PDMA-1 group (PDMA) and the SA-CMC@PAA-1 group (PAA), it was found that PDMA, with its outer gel structure, exhibited a higher swelling ratio and a higher water absorption and swelling capacity compared to PAA.

[0118] 3. Release behavior of contents

[0119] 3.1 Test method

[0120] In order to test the content release behavior of each group of two-layer composite hydrogel microcarriers, a content release test is carried out according to the following flow.

[0121] First, three kinds of contents with different molecular weight and solubility characteristics were selected and mixed with different groups of bilayer composite hydrogel microcarriers, and each content was loaded on the bilayer composite hydrogel microcarriers. For the contents, vitamin A acid (tretinoin; TR) was selected as the fat-soluble component, penicillin (ampicillin; AM) as the water-soluble component, and bovine serum albumin (bovine serum; BS) was selected as the stem cell culture medium component. The concentration of vitamin A acid in the bilayer composite hydrogel microcarriers was 0.5 milligrams / liter, the concentration of penicillin in the bilayer composite hydrogel microcarriers was 100 milligrams / ml, and the weight percentage of bovine serum albumin in the bilayer composite hydrogel microcarriers was 5%. The bilayer composite hydrogel microcarriers loaded with the contents were immersed in an acidic solution with a pH value of 1.2 for 2 hours, and then transferred to a weakly basic solution with a pH value of 7.4 at 36.5°C ± 0.5°C. Then, the bilayer composite hydrogel microcarrier was weighed, immersed in 100 milliliters of PBS, and rotated at an appropriate rotation speed under the condition of 36.5°C ± 0.5°C. A fixed amount of PBS was extracted at regular intervals, and the concentration of the contents was measured with an ultraviolet spectrophotometer (TR measurement wavelength: 350 nanometers, AM measurement wavelength: 463 nanometers, BS measurement wavelength: 595 nanometers), and an equal amount of PBS was replenished. Then, the cumulative release rate Qn of the contents of the bilayer composite hydrogel microcarrier was measured based on the following formula, and the results are summarized in Figures 4A to 6B.

[0122] Qn(%)=(V0Cn+VC(n-1)) / (W)×100

[0123] Cn and C(n-1) are the concentrations of the contents sampled n and n-1 times, V0 is the initial volume of PBS, V is the sampling volume, and W is the weight of the contents loaded onto the two-layer composite hydrogel microcarrier.

[0124] 3.2, Results analysis

[0125] To facilitate understanding of the effects of components, weight percentages, and outer layer crosslinking time on the content release behavior in the two-layer composite hydrogel microcarriers, Figure 4A (SA-CMC@PDMA-2) and Figure 4B (SA-CMC@PDMA-3), Figure 5A (SA-CMC@PDMA-1) and Figure 5B (SA-CMC@PDMA-2), and Figure 6A (SA-CMC@PDMA-1) and Figure 6B (SA-CMC@PAA-1) are discussed later for comparison with each other.

[0126] 3.2.1 Comparison of content release behavior depending on outer layer thickness

[0127] First, referring to Figures 4A and 4B, the two-layer composite hydrogel microcarriers between the two groups differ in that the outer layer crosslinking time is extended from 2 minutes (SA-CMC@PDMA-2 group) to 3 minutes (SA-CMC@PDMA-3 group), increasing the thickness of the outer layer gel structure.

[0128] As can be seen from the results in Figures 4A and 4B, in the initial acidic environment, the two types of bilayer composite hydrogel microcarriers have good sustained release effects for both fat-soluble vitamin A acid (TR) and bovine serum albumin (BS), but do not have the same control effect on water-soluble penicillin (AM). Due to the small molecular weight of AM and its easy diffusion in the solution, a serious release effect occurs on AM. In the SA-CMC@PDMA-2 group, the 2-hour release rate is high at about 90%, while in the SA-CMC@PDMA-3 group, which has a relatively thick outer layer, the 2-hour release rate is high at about 65% due to the increased diffusion resistance, indicating that the thickness of the outer layer still has a release-retarding effect on the water-soluble component AM in the acidic environment.

[0129] In a weakly alkaline environment, the inner gel structure began to absorb water and expand, the network structure collapsed, and vitamin A acid (TR) and bovine serum albumin (BS) were gradually released. In the SA-CMC@PDMA-2 group, the release rate of TR reached more than 90% at 36 hours, while the release rate of BS, which has a relatively large molecular structure, reached only about 64%, indicating that the bilayer structure design has a better sustained release effect on the stem cell culture medium components (represented by BS) than on the fat-soluble components (represented by TR). In contrast, in the SA-CMC@PDMA-3 group, which has a relatively thick outer layer, the release rate of TM decreased to about 80% at 36 hours, and the release rate of BS reached only 35%, indicating that in a weakly alkaline environment, it can better exert the release delay and control effect on the fat-soluble components (TR) and stem cell culture medium components (BS).

[0130] Therefore, as can be seen from Figures 4A and 4B, by increasing the thickness of the outer layer, the diffusion resistance can be improved and the release of the contents can be significantly delayed.

[0131] 3.2.2. Comparison of content release behavior depending on the concentration of the inner layer composition

[0132] See Figures 5A and 5B, the two groups of bilayer composite hydrogel microcarriers differ in the weight percentage of the inner layer polymer (SA-CMC@PDMA-1 group is 1.5% SA / 1.0% CMC, and SA-CMC@PDMA-2 group is 0.5% SA / 2.0% CMC).

[0133] The results in Figures 5A and 5B show that in the initial acidic environment, the sustained release effect of the bilayer hydrogel due to the composition of the inner layer gel structure does not obviously change, and it has good sustained release effect for both fat-soluble vitamin A acid (TR) and bovine serum albumin (BS), while a serious release effect still occurs for water-soluble penicillin (AM), with the 2-hour release rate being as high as 70%-90%.

[0134] In a weakly basic environment, there is no significant difference in the release rates of TR and AM between the two groups, but SA-CMC@PDMA-2 with a relatively low concentration of SA (as exemplified in "1. Gel morphology under electron microscope" by the fact that the pore size of SA-CMC@PDMA-2 is obviously smaller than that of SA-CMC@PDMA-1) has a better control effect on the release of BS.

[0135] Compared with the polymer BS, the lipid-soluble TR and water-soluble penicillin AM are both small molecules. As can be seen from Figures 5A and 5B, the change in the composition of the inner gel structure does not have a significant effect on the small molecule content, but the reduction in the concentration of SA can slow down the diffusion rate of the polymer content and reduce the release rate.

[0136] 3.2.3 Comparison of release behavior of contents depending on the composition of the outer layer

[0137] See Figures 6A and 6B, the bilayer composite hydrogel microcarriers between the two groups differ in the composition of the outer layer monomer (SA-CMC@PDMA-1 group is PDMA, and SA-CMC@PAA-1 group is PAA).

[0138] The results in Figures 6A and 6B show that there is no significant difference in the release rates of lipid-soluble vitamin A acid (TR) and water-soluble penicillin (AM) in the two groups of bilayer composite hydrogel microcarriers, but the release rate of bovine serum albumin (BS) decreases significantly when the component of the outer layer polymer is changed from PDMA to PAA, which has a lower swelling ratio and smaller pore size.

[0139] In other words, when PAA is selected and used as a component of the outer gel structure, as opposed to the selection and use of PDMA, it does not have a significant effect on the small molecule content, but it can slow down the diffusion rate of the polymer content and reduce the release rate.

[0140] 4.Structural strength

[0141] In order to test the relationship between the content of a specific component in the gel structure and the structural strength, a single-layer gel structure was prepared based on the formulation in Table 2 below, substantially similar to step 1.1 of Example 1, and the relationship between the viscosity of the single-layer gel structure and temperature was measured. The results are shown in FIG. 7.

[0142] [Table 2]

[0143] Figure 7 shows that the viscosity of the gel structure increases with increasing concentration of carboxymethylcellulose (CMC) at 37.5°C. It can be seen that when the viscosity of the gel structure increases, the structural strength increases accordingly. Therefore, as the concentration of CMC increases, the structural strength of the gel structure also improves accordingly.

[0144] Furthermore, when the viscosity is close to or higher than 1 Pascal·second (Pa·s) (e.g., SA in group 1 is 5 wt% and CMC is 2 wt%, and SA in group 2 is 5 wt% and CMC is 1 wt%), the structural strength of the gel structure can be suitable for culturing stem cells without easily bursting.

[0145] In contrast, if the viscosity of the gel structure is too low (eg, SA is 5 wt% and CMC is 0.1 wt% in group 3), there is a relatively high risk of the gel structure bursting when it is used for culturing stem cells.

[0146] Therefore, the gel structures of groups 1 and 2, when used as inner layer gel structures (weight percentage of CMC greater than 1 wt%), can provide good structural strength to the bilayer composite hydrogel microcarriers and serve as stem cell growth scaffolds.

[0147] 5. Stem cell culture efficiency

[0148] First, two groups of bilayer composite hydrogel microcarriers with different weight ratios of SA and CMC, namely SA-CMC@PDMA-1 (SA is 1.5% and CMC is 1%) and SA-CMC@PDMA-2 (SA is 0.5% and CMC is 2%) in Table 1, were selected and used to culture adipose stem cells in a manner similar to that of Example 2. At the same time, the culture conditions were divided into groups based on whether or not bovine serum albumin (BSA) was added as a nutrient component, and synchronous observation was performed.

[0149] Later, the following two parts were analyzed to observe whether the bilayer composite hydrogel microcarriers with different component ratios affect the growth efficiency of adipose stem cells when used in the culture of adipose stem cells.

[0150] The first part is mRNA analysis. After culturing the adipose stem cells for 7 days, the mRNA expression ratio of adipose stem cell specific protein (lipoprotein lipase; LPL) and cell general protein (glyceraldehyde-3-phosphate dehydrogenase; GAPDH) was analyzed to determine the growth status of adipose stem cells. The higher the ratio, the higher the content of adipose stem cells. The results are shown in Figure 8A.

[0151] Figure 8A shows that SA-CMC@PDMA-1 (SA 1.5% + CMC 1%) both have favorable adipose stem cell growth efficiency compared with SA-CMC@PDMA-2 (SA is 0.5% and CMC is 2 wt%), whether BSA is added or not.

[0152] The second part is the observation in the microscope field. The number of cells growing in the microscope field after culturing the adipose stem cells of each group for 7 days was observed by a microscope. The adipose stem cells were recognized by CD44 monoclonal antibody and stained with Oil Red O, and turned reddish purple. The higher the proportion of reddish purple, the higher the content of adipose stem cells. The results are shown in Figure 8B.

[0153] Figure 8B shows that when macromolecular nutrient molecules (BSA) were added, the percentage of adipose stem cells was higher in SA-CMC@PDMA-1 (SA 1.5% + CMC 1%) than in SA-CMC@PDMA-2 (SA 0.5% and CMC 2wt%). In other words, when nutrients were added, the weight ratio conditions of SA-CMC@PDMA-1 were adopted to achieve high stem cell culture efficiency.

[0154] In the method for culturing stem cells using the bilayer composite hydrogel microcarrier provided by some embodiments of the present disclosure, the inner layer gel structure and the outer layer gel structure can be designed to provide physical support to the inner layer gel structure, avoid the effect of acid-base on the structure, improve the diffusion resistance, and delay the release of nutrients. By defining the weight ratio of sodium alginate and carboxymethylcellulose and the location of nutrients, the pore size of the inner layer gel structure can be controlled, and the rate at which nutrients are released from the bilayer composite hydrogel microcarrier can be adjusted and controlled, allowing stem cells to stably take in nutrients and improving the growth rate of stem cells. By controlling the weight percentage of carboxymethylcellulose, the structural strength of the bilayer composite hydrogel microcarrier can be ensured and it can be used as a growth scaffold for stem cells.

[0155] The present disclosure has been disclosed as above by the embodiments, but the embodiments are not intended to limit the present disclosure, and those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present disclosure. Therefore, the scope of protection of the present disclosure is based on the contents specified in the following claims.

Claims

1. Providing stem cells, bilayer composite hydrogel microcarriers and nutritional components; mixing the stem cells, the bilayer composite hydrogel microcarriers and the nutritional components to obtain a gelling medium; adding a culture medium to the gelling medium; Including, The bilayer composite hydrogel microcarrier comprises: an inner layer gel structure obtained by ionically cross-linking the inner layer polymer with an inner layer cross-linked material; an outer layer gel structure obtained by covalently crosslinking and polymerizing an outer layer monomer with an outer layer crosslinked product, the outer layer gel structure covering the inner layer gel structure; Including, the inner layer polymer comprises a first inner layer polymer and a second inner layer polymer, the first inner layer polymer being sodium alginate and the second inner layer polymer being carboxymethylcellulose, the weight ratio of the sodium alginate to the carboxymethylcellulose being 3:2, and the weight percentage of the carboxymethylcellulose being greater than 1% when the weight percentage of the inner layer gel structure is 100%; A method for culturing stem cells using a bilayer composite hydrogel microcarrier, wherein the nutritional components are located inside the inner layer gel structure.

2. 2. The method of claim 1, wherein the stem cells comprise embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or a combination thereof.

3. the inner layer gel structure is a plurality of inner layer sheet-like structures connected to each other and separated from each other by a plurality of inner layer holes; 2. The method of claim 1, wherein the outer layer gel structure is a plurality of outer layer sheet-like structures that are connected to each other and separated from each other by a plurality of outer layer pores having a pore size smaller than the pore size of each of the inner layer pores.

4. The method of claim 1 , wherein the inner layer gel structure is an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.

5. The method of claim 1 , wherein the inner layer polymer and the inner layer crosslinked material have opposite electrical properties.

6. The method of claim 1 , wherein the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide, or a combination thereof.

7. The method of claim 1 , wherein the outer layer crosslinked material comprises N,N'-methylenebisacrylamide.

8. 2. The method of claim 1, wherein the weight percentage of the sodium alginate is between 0.1% and 5%, when the weight percentage of the inner layer gel structure is 100%.

9. 2. The method of claim 1, wherein the weight percentage of the carboxymethyl cellulose is between 1% and 5%, based on the weight percentage of the inner layer gel structure being 100%.

10. 10. The method of claim 1, wherein the nutritional ingredients include growth factors, vitamin A acid, penicillin, bovine serum albumin, or combinations thereof.

11. providing stem cells, bilayer composite hydrogel microcarriers, and a nutritional component comprising a macromolecular protein having a molecular weight greater than at least 500 grams / mole; mixing the stem cells, the bilayer composite hydrogel microcarriers and the nutritional components to obtain a gelling medium; adding a culture medium to the gelling medium; Including, The bilayer composite hydrogel microcarrier comprises: an inner layer gel structure obtained by ionically cross-linking the inner layer polymer with an inner layer cross-linked material; an outer layer gel structure obtained by covalently crosslinking and polymerizing an outer layer monomer with an outer layer crosslinked product, the outer layer gel structure covering the inner layer gel structure; Including, the inner layer polymer comprises a first inner layer polymer and a second inner layer polymer, the first inner layer polymer is sodium alginate, the second inner layer polymer is carboxymethylcellulose, and a weight ratio of the sodium alginate to the carboxymethylcellulose is 3:2; A method for culturing stem cells using a bilayer composite hydrogel microcarrier, wherein the nutritional components are located inside the inner layer gel structure.

12. 12. The method of claim 11, wherein the stem cells comprise embryonic stem cells, hematopoietic stem cells, mammary stem cells, mesenchymal stem cells, endothelial stem cells, neural stem cells, olfactory stem cells, adipose stem cells, or a combination thereof.

13. the inner layer gel structure is a plurality of inner layer sheet-like structures connected to each other and separated from each other by a plurality of inner layer holes; 12. The method of claim 11, wherein the outer layer gel structure is a plurality of outer layer sheet-like structures that are connected to each other and separated from each other by a plurality of outer layer pores having a pore size smaller than the pore size of each of the inner layer pores.

14. The method of claim 11 , wherein the inner layer gel structure is an interpenetrating structure of the first inner layer polymer and the second inner layer polymer.

15. The method of claim 11 , wherein the inner layer polymer and the inner layer crosslinked material have opposite electrical properties.

16. The method of claim 11 , wherein the outer layer monomer comprises N,N-dimethylacrylamide, acrylamide, or a combination thereof.

17. The method of claim 11 , wherein the outer layer crosslinked material comprises N,N′-methylenebisacrylamide.

18. 12. The method of claim 11, wherein the weight percentage of the sodium alginate is between 0.1% and 5%, when the weight percentage of the inner layer gel structure is 100%.

19. 12. The method of claim 11, wherein the weight percent of the carboxymethyl cellulose is greater than 1%, based on the weight percent of the inner layer gel structure being 100%.

20. 20. The method of claim 19, wherein the weight percentage of the carboxymethyl cellulose is between 1% and 5%, based on the weight percentage of the inner layer gel structure being 100%.

Citation Information

Patent Citations

  • Carrier for cell culture

    JP2022142482A